PENGARUH CURRENT RATIO DAN DEBT TO ASSET RATIO TERHADAP NET PROFIT MARGIN PADA PT ADHI KARYA TBK TAHUN 2013-2022 - Wulandari, Iluh; Nofiana, Lina (Journal of Research and Publication Innovation, 2024)
This research aims to examine several variables, namely the Current Ratio and Debt to Asset Ratio, found in financial statements that influence the Net Profit Margin variable. The study was conducted on a construction company listed on the Indonesia Stock Exchange from 2013 to 2022. The research method uses multiple linear regression analysis with F-test and T-test. The R-squared value is 0.739 or 73.9% of the total profit. The results of this study indicate that the Current Ratio variable has an effect on the Net Profit Margin, with a t-value of 3.769 > t-table 2.364 and a significance value of 0.007 < 0.05, whereas the Debt to Asset Ratio does not have a significant effect on the Net Profit Margin, with a t-value of 0.633 < t-table 2.364 and a significance value of 0.547 > 0.05. All the independent variables used in this research, the Current Ratio and Debt to Asset Ratio, simultaneously influence the dependent variable, Net Profit Margin, with an F-value of 9.885 > F-table 4.46 and a significance value of 0.009 < 0.05.